Identification of genetic overlaps for salt and drought tolerance using simple sequence repeat markers on an advanced backcross population in rice - Yun, W.; Jinping, Z.; Yong, S.; Jauhar, A.; Jianlong, X.; Zhikang, L. (Wiley, 2012)
Salinity and drought are two of the major abiotic stresses that affect rice (Oryza sativa L.) production especially in Asia. Quantitative trait loci (QTL) for salt tolerance (ST) at seedling stage and drought tolerance (DT) at reproductive stage were identified using 77 BC2F8 advanced backcross introgression lines (ILs) derived from a cross of Teqing × Binam in Teqing background. Ten ST QTL were identified governing days to seedlings survival (DSS), score on salt toxicity symptoms on leaves (SST), shoot K+ concentration (SKC), and shoot Na+ concentration (SNC) at seedling stage, and 23 QTL were identified under reproductive stage drought and irrigated conditions for panicle number per plant (PN), thousand grain weight (TGW), seed fertility (SF), plant height (PH), and grain yield per plant (GYP). Most QTL detected at reproductive stage showed obvious differential expression to drought stress. In addition, another eight QTL were detected by trait ratio of the stress to the irrigation; the alleles at all loci except QSf3 showed increasing trait values to be associated with Binam, indicating Binam alleles at these loci could improve DT under drought stress. Upon comparison of identified ST and DT QTL we found 14 QTL shared the same genome regions with similar gene actions, clearly suggesting that genetic overlap existed between the two abiotic stress tolerances. Pyramiding of favorable alleles from Binam into Teqing background should allow us to develop superior ILs with higher levels of ST and DT.